2019
DOI: 10.3390/genes10020105
|View full text |Cite
|
Sign up to set email alerts
|

Single and Double Strand Sperm DNA Damage: Different Reproductive Effects on Male Fertility

Abstract: Reproductive diseases have become a growing worldwide problem and male factor plays an important role in the reproductive diagnosis, prognosis and design of assisted reproductive treatments. Sperm cell holds the mission of carrying the paternal genetic complement to the oocyte in order to contribute to an euploid zygote with proper DNA integrity. Sperm DNA fragmentation had been used for decades as a male fertility test, however, its usefulness have arisen multiple debates, especially around Intracytoplasmic S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(116 citation statements)
references
References 107 publications
4
109
0
3
Order By: Relevance
“…It has been reported that massive SSBs can potentially decrease the probability of pregnancy or increase the time to achieve conception, whereas a relatively small number of DSBs presumably located at attachment sites to the sperm nuclear matrix can adversely influence embryo kinetics and implantation rate and increase the risk of recurrent miscarriage during the first trimester 54 . Nevertheless, this distinction between massive SSBs and DSBs in predicting reproductive outcome needs to be regarded with caution.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that massive SSBs can potentially decrease the probability of pregnancy or increase the time to achieve conception, whereas a relatively small number of DSBs presumably located at attachment sites to the sperm nuclear matrix can adversely influence embryo kinetics and implantation rate and increase the risk of recurrent miscarriage during the first trimester 54 . Nevertheless, this distinction between massive SSBs and DSBs in predicting reproductive outcome needs to be regarded with caution.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, SSBs do not significantly impact embryo development or implantation rates [117]. Nonetheless, higher levels of SSBs are inversely related to the natural pregnancy outcome [118]. Thus, evaluation of SSB and DSB may provide important information during fertility evaluation of men [119].…”
Section: Sperm Dna Fragmentation: Single-versus Double-strand Breaksmentioning
confidence: 99%
“…Although it is difficult to establish which percentages of infertile patients have an underlying mechanism of oxidative stress, it is known that it could be present as a factor in asthenozoospermic, teratozospermic, and oligozoospermic patients who present reproductive issues [77,78]. All these parameters have been associated in different studies with a reduction in natural pregnancy, both in animal [79,80] and human studies [76,81,82], supporting the evidence that oxidative stress leads to a reduction in natural fertility rates [77,83].…”
Section: Natural Pregnancymentioning
confidence: 80%
“…In this context, however, it is worth mentioning that detecting these DNA breaks and its type heavily relies upon the sensitivity of the technique used to evaluate sperm DNA fragmentation (i.e., SCSA, SCDt, TUNEL, neutral Comet, alkaline Comet, etc. ), which leads to different correlations to clinical outcomes [76].…”
Section: Sperm Dna Damagementioning
confidence: 99%